Pengaruh Country Of Origin terhadap Perceived Quality Dengan Moderasi Etnosentris Konsumen - Listiana, Erna (Jurnal Administrasi Bisnis, 2012)
In recent times, more and more foreign brands fluttering in the Indonesianmarket and competing with local brands. Often the consumers give a response onthe country of origin (COO) aspect to provide an assessment of the quality brandsoriginating from that country. Magnitude of this effect will usually vary depending onthe level of consumer ethnocentric. This study was conducted to determine how theIndonesian consumer ethnocentric role in moderating influence consumer perceptionof COO into perceived quality. Research will be focused on the type of electronicproduct categories of laptops and notebooks. Brand laptop / notebook in question wasderived from one of the following countries: USA, Japan, Korea, Taiwan and China.Results show that the data analyst of COO gives a significant effect on the perceivedquality in both groups of respondents with high and low levels of ethnocentric. Effectof the COO onto the perceived quality is greater for the low ethnocentric group ofrespondents (56,6 %) than in the group of high ethnocentric respondents (30,5 %).Keywords: Country of Origin, Perceived Quality, Consumer Ethnocentrism